Test Some Concentration of Bacillus subtilis to Increase the Resistance of Tomato Plants to Xanthomonas campestris pv. vesicatoria: Uji Beberapa Konsentrasi Bacillus subtilis untuk Meningkatkan Ketahanan Tanaman Tomat terhadap Xanthomonas campestris pv. vesicatoria - Aulia, Nadrah Rahmatika; Fifi Puspita (Talenta Publisher, 2023)
The aim of this study is to know the effect of several concentrations of Bacillus subtilis and to obtain a concentration capable of inducing tomatoes from attack by Xanthomonas campestris pv. vesicatoria. This study was conducted experimentally using a completely randomized design (RAL) with 5 treatments and 4 replications. The treatment used was the concentration of Bacillus subtilis which consisted of B0 = no use of Bacillus subtilis, B1 = concentration of Bacillus subtilis 106 cells.ml-1, B2 = concentration of Bacillus subtilis 107 cells.ml-1, B3 = concentration of Bacillus subtilis 108 cells.ml-1, B4 = concentration of Bacillus subtilis 109 cells.ml-1. The parameters observed were the number of colonies of Bacillus subtilis in the growth medium, the concentration of salicylic acid content, disease intensity, plant height, stem diameter, and weight of fruit. The results showed that the concentration of Bacillus subtilis in each treatment was able to induce tomato plant resistance to Xanthomonas campestris pv. vesicatoria and gave significantly different results on the number of colonies on soil medium, the concentration of salicylic acid content, disease intensity, plant height, steam diameter, and weight of fruit.